1996
DOI: 10.1111/j.1600-0722.1996.tb00096.x
|View full text |Cite
|
Sign up to set email alerts
|

A 3‐year clinical study of tunnel restorations

Abstract: Tunnel restorations (n = 161) performed by 4 dentists were evaluated after a mean of 35 months in situ. Demineralized enamel was to be spared during preparation. The preparations were filled with a cermet glass ionomer (polyalkenoate) cement. Evaluation was carried out using clinical and radiographical criteria. During the observation period, approximately 16% of the restorations were replaced due to caries in dentin and 14% due to marginal ridge fracture. Cavitation in the approximal surface and/or increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 12 publications
0
16
1
3
Order By: Relevance
“…Recently, different cavity models were investigated by the use of Finite Element Analysis [57], and it was concluded that in class I and small class II MO cavities maximum stresses were generated along the toothrestoration interface basically due to this lack of wall deformation. These observations were also confirmed in vivo [11,40,43,54]. In addition to the C-factor, lack of wall elasticity seems to be a critical issue that should be addressed in further investigations.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, different cavity models were investigated by the use of Finite Element Analysis [57], and it was concluded that in class I and small class II MO cavities maximum stresses were generated along the toothrestoration interface basically due to this lack of wall deformation. These observations were also confirmed in vivo [11,40,43,54]. In addition to the C-factor, lack of wall elasticity seems to be a critical issue that should be addressed in further investigations.…”
Section: Discussionmentioning
confidence: 54%
“…New techniques, like saucer-shaped and tunnel preparation, have been developed to allow minimal substance removal [Peters and McLean, 2001]. Unfortunately, tunnel preparations have been proven unsuccessful [Strand et al, 1996;Hasselrot, 1998;Pilebro et al, 1999;Nicolaisen et al, 2000;Strand et al, 2000].…”
mentioning
confidence: 99%
“…This should theoretically not affect sensitivity while the false positive fraction might be increased. The prevalence in this study may reflect the situation in clinical studies where 'recurrent' caries has been observed in connection with 13-38% of the filled tunnels in permanent teeth [Svanberg, 1992;Nordbø et al, 1993;Lumely and Fisher, 1995;Strand et al, 1996]. These figures may include false positive and exclude false negative registrations, and the true fraction of teeth with caries may therefore be lower or higher.…”
Section: Caries Detection In Tunnel Restorationsmentioning
confidence: 84%
“…However, laboratory and clinical studies have revealed various problems in relation to the tunnel restoration. Primarily, the problems have been ascribed to the presence of residual dentinal caries, recurrence of the lesion and marginal ridge fracture [Strand and Tveit, 1993;Hasselrot, 1993;Strand et al, 1996].…”
mentioning
confidence: 99%